Korelasi Konsep Diri Dengan Perilaku Konformitas Penggunaan Aplikasi TikTok Kelas XII SMA Semen Padang - Yomi Muhaimi; Linda Fitria; Indra Wijaya (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
Self-concept is a person's understanding, image or perception of themselves, a person views and assesses their physical condition, such as appearance, health, fitness, views and assesses their role in the social environment, relationships with others, and social acceptance. This study aims to determine the magnitude of the relationship between self-concept and students' conformity behavior. The method used in this study is quantitative with the type of research, namely correlational. The study was conducted in class XII of SMA Semen Padang. The population of this study was 150 people with a sample of 109 in the 2024/2025 academic year. The sampling technique used was the purposive sampling technique. The instrument in this study was a Likert scale questionnaire. Data analysis using statistical programs on IBM Statistical 29 and Microsoft Excel computers. Based on the results of data processing, the r-count value is 0.107, while the value is 0.195 because the r-count value is smaller than the r-table value (0.107 <0.195), it is concluded that there is no significant relationship between self-concept and conformity behavior.